Anthiypercholesterolaemic Activity of Zincophyllin - . Alsuhendra; D Muchtadi; D Sastradipradja; T Wresdiyati (Jurnal Teknologi dan Industri Pangan, 2003)
Pheophytin was obtained from chlorophyll that was extracted from fresh cassava leaves by use of ethanol. One hundred to 200 ppm of zinc was added to pheophytin to produce a complex of zinc-pheophytin (“zincophyllin”). The antihypercholesterolaemic effect of “zincophyllin” was studied in 20 male New Zealand White rabbits fed on a low-cholesterol (0.1%) diet for 12 weeks. Five animals were given 33.4 mg/d (doses I), 5 animals received 100.2 mg/d (doses II) of “zincophyllin”, 5 animals received standard diet as negative controls, and the remaining 5 animals served as cholesterol-fed controls (positive controls). Animal receiving dose Ii had significantly lower serum total and LDL-cholesterol concentrations. Positive control group and doses I group had significantly higher serum total cholesterol. Cholesterol concentration of group II slightly increased for 4 weeks, but decreased to normal until 12 weeks. Triglyceride concentration of all rabbits groups were in normal level, but LDL-cholesterol concentration of positive control group and doses I group were higher than others. It was suggested that the antihypercholesterolaemic effect of “zincophyllin” may benefit rabbits by inhibiting the increase of serum cholesterol concentration. Key words: Chlorophyll, pheophytin, “zincophyllin”, hypercholesterolaemic